Evidence-based intervention to prevent anemia among women of reproductive age group in developing countries - Mubashir Zafar (Wolters Kluwer Medknow Publications, 2020)
Background and Objective: Anemia in developing countries is the biggest public health problem. Reproductive age group women have high prevalence. The objective of the present study is to determine the cost-effective intervention for the reduction of anemia among women of reproductive age group. Methodology: A review of the literature was done for identifying various preventive strategies regarding anemia and its implementation barriers in low- and middle-income countries. Google Scholar, PubMed, Web of Science, and Scopus were used as search engines.Results: The result of the review shows that the most cost-effective method for the prevention of anemia among women is iron fortification of food, iron supplementation, community-based health promotion of healthy nutrition. Women empowerment is the best tool for the implementation of all the above method for the prevention of anemia. Conclusion: Community-based intervention is the most effective method for reducing maternal anemia. It includes health promotion and women empowerment. There is a need to develop policies to improve the health promotion activities and involvement of women in society.